Answer:
y= -3/2x + 12
Explanation:
When finding a perpendicular line you take your slope and make it the opposite (flip it and change the sign).
Slope originally=2/3
New slope= -3/2
Next we will use the point slope equation
y-y1=m(x-x1)
y1=y value
m=slope
x1=x value
y--6= -3/2(x-12) Since you have y minus negative 6 you get to change it to y+6
y+6= -3/2(x-12) Now distribute your slope to both terms inside the parenthesis.
y+6= -3/2(x) -3/2(-12)
y+6= -3/2x +18 Finally subtract 6 from both sides.
-6 -6
y= -3/2x + 12